KEBIJAKAN REFORMASI TERITORIAL DAN PELUANG PEMEKARAN DAERAH DI SULAWESI TENGAH - Djaelangkara, Rizali (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2018)
In the development of government and territorial growth of a region in a country there are three things that are likely to occur related to territorial / regional structuring reform policies, first, the area is broader because the second centripetal policy has merged or annexed due to fragmentation. territorial (centrifugal policy), third, with the same territorial area (static / constants policy). in post-reform Indonesia in 1998 there have been an increase of 223 new autonomous regions (DOB) from a total of 319 pre-reform autonomous regions to 542 autonomous regions at the provincial / district / city level after the reformation. For Central Sulawesi, there are 23 proposals / plans for the establishment of DOBs. For projections and strategies to address the issue of regional expansion in Central Sulawesi based on current conditions and dynamics (2018), appropriate policy choices are needed in the face of the growing phenomenon of demand for expansion / formation of DOBs and regional structuring strategies based on centripetal policy, centrifugal policy or Constants policy . Judging from the strength of the Centripetal policy (integrated direction) there are a number of choices in the form of Annexation, Consolidation, Amalgamition. While the Centrifugal policy in the form of policies of Detachment, Fragmentation, Proliferation, Regional Government Splitting, Partition and Political Sub Division. For Constants / static policy choices in which the government carries out a pemekaran moratorium on an ongoing basis with proactive policy instruments. To project opportunities for DOB formation in Central Sulawesi, (1) Proposal for the establishment of Moutong and Tomini Raya Districts is more likely to be realized, as seen from the process, the two DOB candidates have been approved as DOBs as proposed by the DPR-RI initiative. East has the opportunity, because the proposal of the area at the regional level has been completed. (3) Areas that are actually and factually truly for reasons of distance of service and / or because of consideration of having national strategic values and security can have opportunities for form.